Efek Pandemi Covid-19 Terhadap Kesehatan Mental Pada Populasi Umum - Naisya Midary Mutia Pratiwi (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT The 2019 Coronavirus disease (COVID-19) pandemic is the largest viral outbreak of this century. The COVID-19 pandemic had an unprecedented impact on mental health. Prevention of infection to control the spread of this epidemic requires restrictions on physical activity that took place in Indonesia within the last 2 years. Analyze the impact of the COVID-19 pandemic on mental health in the general population and health workers and the associated risk factors. The method used is literature review where data is obtained from several electronic databases such as google scholar, PubMed, and NCBI between 2019-2022. 20 of 41 articles are selected based on predetermined eligibility criteria. Mental health problems in the general public during COVID-19 were reported to have quite high numbers, namely anxiety (6.33% - 50.9%), depression (14.6%-48.3%), PTSD (7%-53, 8%), stress (8.1%-81.9%). The associated risk factors are female gender, young age (<40 years), chronic/psychiatric disease, unemployment, students, and frequent exposure to COVID-19 news. The COVID-19 pandemic had a very significant effect on the level of psychological distress. Therefore, special attention is needed to the prevention and treatment of mental health disorders to help the community through this pandemic. Keywords: COVID-19, Pandemic, Mental Health, Risk Factors  ABSTRAK Pandemi Coronavirus disease 2019 (COVID-19) merupakan wabah virus terbesar pada abad ini. Pandemi COVID-19 telah menghasilkan dampak yang tidak pernah diperkirakan sebelumnya terhadap kesehatan mental. Pencegahan infeksi untuk mengendalikan penyebaran wabah ini mengharuskan adanya pembatasan aktivitas fisik yang berlangsung di Indonesia dalam kurun waktu 2 tahun terakhir. Menganalisis dampak pandemi COVID-19 terhadap kesehatan mental pada populasi umum dan petugas kesehatan serta faktor risiko yang berhubungan. Metode yang digunakan adalah studi literatur dimana data diperoleh dari beberapa database elektronik seperti google schoolar, PubMed, NCBI antara tahun 2019-2022. 20 dari 41 artikel dipilih berdasarkan kriteria kelayakan yang telah ditentukan. Masalah kesehatan mental pada populasi umum selama COVID-19 dilaporkan memiliki angka yang cukup tinggi yakni kecemasan (6,33% - 50,9%),depresi (14,6%-48,3%), PTSD (7%-53,8%), stress (8,1%-81,9%). Faktor risiko yang berhubungan yakni jenis kelamin perempuan, usia yang muda (<40 tahun), adanya penyakit kronis/psikiatri, pengangguran, pelajar, dan sering terpapar berita COVID-19. Pandemi COVID-19 memiliki efek yang sangat signifikan pada  tingkat tekanan psikologis. Oleh karena itu, diperlukan perhatian khusus terhadap pencegahan dan penanganan gangguan kesehatan mental untuk membantu populasi melalui pandemi ini. Kata Kunci: COVID-19, Pandemi, Kesehatan Mental, Faktor Risiko